2018
DOI: 10.1038/s41467-018-07806-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 modulates thymic-derived regulatory T cell epigenetic landscape

Abstract: Foxp3+CD4+ regulatory T (Treg) cells are essential for preventing fatal autoimmunity and safeguard immune homeostasis in vivo. While expression of the transcription factor Foxp3 and IL-2 signals are both required for the development and function of Treg cells, the commitment to the Treg cell lineage occurs during thymic selection upon T cell receptor (TCR) triggering, and precedes the expression of Foxp3. Whether signals beside TCR contribute to establish Treg cell epigenetic and functional identity is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…SATB1 is predominantly expressed in the thymus and highly associated with thymocyte differentiation. It is thought to induce lymphopoiesis and regulate the expression of various genes during lymphocyte especially T cell development, so SATB1 is thought to be correlated to the development of ALL [1822, 28, 31, 3540]. SATB1 regulates many genes involved in HSC lineage decisions and development, but evidence that supports the role of SATB1 in AML remained elusive [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 is predominantly expressed in the thymus and highly associated with thymocyte differentiation. It is thought to induce lymphopoiesis and regulate the expression of various genes during lymphocyte especially T cell development, so SATB1 is thought to be correlated to the development of ALL [1822, 28, 31, 3540]. SATB1 regulates many genes involved in HSC lineage decisions and development, but evidence that supports the role of SATB1 in AML remained elusive [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Whether a 129‐derived passenger mutation, a mutation in the ESC clone used for Ackr4 −/− generation or a spontaneous mutation acquired in a subcolony of Ackr4 −/− mice is responsible for the unexplained phenotype remains elusive. For all three scenarios, examples have been reported for other transgenic mice …”
Section: Discussionmentioning
confidence: 79%
“…We detected a larger amount of distal genes ( n = 319) compared with local genes ( n = 35), including 148 distal genes exclusively regulated by distal functional SNPs ( Figure 5A and Supplemental Table 7 ). These exclusive distal genes included many known immunologic genes, such as CD37 ( 45 ), CD28 ( 46 ), IL7 ( 47 ), IL12RB1 ( 48 ), or IL2RA ( 49 ). Previous functional assays have demonstrated that some distal immune-relevant genes could be regulated by distal enhancers in immune cell types, such as IL2RA ( 50 ), CD58 ( 51 ), IRF1 ( 52 ), or IRF5 ( 20 ), indicating the important roles of long-range regulation on autoimmune diseases.…”
Section: Resultsmentioning
confidence: 99%